EFFECT OF PSYCHOSOCIAL INTERVENTION BY HEALTH WORKERS ONANXIETY LEVELS IN NATURAL DISASTER VICTIMS: SCOOPING REVIEW - Juniartika; Ajengsy Baruadi; M. Saudri Nujumun Sitepu; Ajengsy Febiola Baruadi (Journal of Indonesian Anesthesiology Nursing, 2025)
Abstract Natural disasters cause high levels of anxiety and trauma in survivors. This study aims to synthesize the effectiveness of psychosocial interventions to reduce this anxiety. Background: Natural disasters trigger widespread psychological impacts such as anxiety, depression, and PTSD. Approximately half of survivors experience symptoms of anxiety and trauma post-disaster. Psychosocial interventions are a key approach to reducing anxiety, increasing adaptability, and accelerating trauma healing, thereby preventing long-term mental health problems. Methods: A systematic review design was used to synthesize 11 primary research articles (2011–2025) to analyze the impact of interventions on disaster anxiety. The results showed that all psychosocial interventions were significantly effective in reducing anxiety and stress levels and increasing psychological resilience in disaster survivors. Conclusion: Psychosocial interventions by health workers are an effective and scientifically proven strategy for the mental health recovery of natural disaster victims.